PENYALAHGUNAAN WEWENANG DALAM TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH PENDAMPING SOSIAL PROGRAM KELUARGA HARAPAN (PKH) - Dimas Rangga Kusuma Aji; Ahmad Mahyani (Gapenas Publisher, 2022)
In the midst of Indonesia's economic crisis and the increasing number of poverties, which is triggered by corruption. Corruption can endanger the stability and security of society, economy, politics and can damage the democratic values ??and morality of a country. From a legal point of view, corruption is an extraordinary crime (extraoredinary crimes) and there are also opinions that say that corruption is also a crime against humanity (crimes against humanity) which until now has only become the Ius Constituendum. The practice of criminal acts of corruption has been increasing in recent years. Suspects or defendants from the perpetrators of this crime are no longer limited to the executive and also the legislature and the judiciary. There is one case which is an act of misuse of funds in one of these types of social assistance, one of which is in Malang City, where there is a case of embezzlement of social assistance funds (bansos) for the Family Hope Program (PKH) carried out by Penny Tri Herdhiani (28) who is a PKH assistant in Kanigoro Village, Pagelaran District. Embezzlement is carried out by not providing a Prosperous Family Card (KKS) to KPM (Beneficiary Families) who have died and have moved places/addresses as well as withdrawing some of the PKH funds belonging to KPM. So that this action can be said as an abuse of authority. The abuse of authority is not only carried out by state officials who have high positions or strategic positions but also spreads to remote areas by regional officials. Abuse of authority is stated in Article 3 of Law no. 31 of 1999 concerning the Eradication of Corruption Crimes Jo. UU no. 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption. So that this research will be able to answer the formulation of the problem regarding the concept of abuse of authority and the concept of violating the law in cases of criminal acts of corruption, as well as the application of material criminal law to criminal acts of corruption in the Family Hope Program (PKH) funds in Malang City in Decision Number 119/Pid-Sus- TPK/2021/PN Sby